2011
DOI: 10.3109/07420528.2011.567425
|View full text |Cite
|
Sign up to set email alerts
|

Human Cone Light Sensitivity and Melatonin Rhythms Following 24-hour Continuous Illumination

Abstract: This study investigates the possibility of an endogenous circadian rhythm in retinal cone function in humans. A full-field cone electroretinogram (ERG) was performed every 2 h for 24 h under continuous rod-saturating ambient white light (53 ± 30 lux; pupils dilated) in nine healthy subjects. Distinct circadian variations were superimposed upon a gradual decrease in cone responsiveness to light, demonstrated most reliably in the implicit times of b-wave and oscillatory potentials, and to a lesser extent in ampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 38 publications
1
14
0
2
Order By: Relevance
“…32 These and other studies lend support to the notion that there is a circadian modulation of the sensitivity of the nonvisual light photoreception system to light as already has been shown for the visual photoreceptive system. [33][34][35] Given that melanopsin is the primary circadian photoreceptor, we hypothesize that the intrinsic melanopsin-mediated pupil response may show a 24-hour variation that is influenced by the circadian clock and, therefore, will persist under constant dim lighting conditions. In our study, we addressed the question of whether the PLR varies with time of day.…”
mentioning
confidence: 99%
“…32 These and other studies lend support to the notion that there is a circadian modulation of the sensitivity of the nonvisual light photoreception system to light as already has been shown for the visual photoreceptive system. [33][34][35] Given that melanopsin is the primary circadian photoreceptor, we hypothesize that the intrinsic melanopsin-mediated pupil response may show a 24-hour variation that is influenced by the circadian clock and, therefore, will persist under constant dim lighting conditions. In our study, we addressed the question of whether the PLR varies with time of day.…”
mentioning
confidence: 99%
“…Moreover, those gene expressions fluctuate throughout the day. In physiological experiments, Danilenko et al (2011) recorded light adapted electroretinogram (ERG), and found that the b-component of ERG shows a marked circadian rhythm which peaks at 20:00 hours in human subjects. The b-component of ERG reflects intake into retinal Mü ller cells of potassium ions, which are pumped out from ON-type retinal bipolar cells.…”
Section: Discussionmentioning
confidence: 99%
“…Many of them have been shown to remain rhythmic in constant conditions and, hence, to be regulated by a circadian clock: this is the case for melatonin and DA synthesis, 75 phagocytosis of photoreceptor outer segments, 1 amplitude of the photopic ERG, 35,76 contrast sensitivity, 77 and rod-cone coupling. 78 Since the demonstration of the existence of an autonomous clock in the mammalian retina, 4 it has been essentially assumed that the rhythmic retinal functions are under the control of the retina clock seen as a whole.…”
Section: Functions Controlled By the Retina Clockmentioning
confidence: 99%